Challenges of the internet versus private international law - Monge Talavera, Luz (2023)
The ubiquity of Internet favors, as never imagined in the history of Law, the birth of countless cross-border private relationships. At the same time, it would seem that the rules of Private International Law cannot be applied to the sphere of cyberspace. This article confronts the universality and intangibility of Internet, to the connection factors based on the geographical division into sovereign States that constitute the axis of Private International Law. Will the Internet demand new categories of legal connecting factors from us? “ciberlex”, “lex electronica”, ¿quo vadis lex?